Formation of nano-structured coatings with superhydrophobic properties - Shao, Qi. (2009)
Superhydrophobic surfaces, with a liquid contact angle greater than 150°and hysteresis less than 10°, have drawn a lot of attentions both in academic and in industry because of the self-cleaning properties. Many biological surfaces, such as lotus leaf, exhibits a hierarchically structures surface roughness which is optimized for superhydrophobicity through nature selection. In this report, surfaces with hierarchical structures of sol-gel thin films are fabricated by combination of templation and sol gel methods. The influence of roughness on superhydrophobicity at different length scale is demonstrated by the investigation of static contact angle, hysteresis, and tendency of air trapping formation as well as rough profile analysis. The results indicate that a proposed roughness parameter R2 is able to predict the propensity of air trapping formation from Cassie-Baxter state. With consideration of roughness profile, general design guidelines are suggested in this work. Moreover, coating’s durability is also tested by abrasion tester.